Nexus: da relacionalidade do princípio à metafísica do inominável em Nicolau de Cusa - Teixeira Neto, José (2012)
We indicate the idea of nexus or conexio, thought of as intelligible connection with the intelligent, the foundation on which the reason why you can understand and name, even if inadequately, what the intellect sees incomprehensible and unnameably. Thus, it opens a way for our research: we will take the idea of nexus as fundamental to the interpretation of the divine names and the "metaphysics of the unnameably" and we show how the divine names, mainly in possest, mirrored in the Trinity, relatedness of the principle and therefore also the nexus. For that you need to think some preliminary questions: we will place Nicholas of Cusa in the tradition of medieval Christian Neoplatonism, we resume some discussions on the problem of naming and the philosophy of language in his thinking, we will reflect such thinking is molded from active dialogue with the tradition and how it is your speculation is founded upon the dynamic and dialectical relationship between philosophy and theology to be thought of in our text using the relationship between faith and understandig (intellectus). After introductory clarify these issues we will come to consider introductory understanding of the Trinitarian Beginning and speculation about the nexus taking as its starting point from where the De venatione sapientiae nexus or conexio is designed as a hunting field of wisdom and the First Book of De docta ignorantia where the maximum is now thought of as one and triune. From the Second Book of the same work and the Idiota. De mente we will show in what sense the universe and men, as imago dei, imitate the eternal Trinity. Finally, we will resume the notion of the scientia aenigmatica of De beryllo and some information that will clarify that Nicholas assumes the divine names as enigmas. Finally, we will try to show that the enigmatic or symbolic names also mirror the triune Beginning principle. So, before we return some traces of this aspect in some divine names and texts of the "late period" and then conclude with that which in itself already indicates the nexus and therefore the trinity: possest